Practical And Advanced Color Mixing Machine For Achieving Your Desired Color Palette - Aljboor, Jibreen; Talahema, Mohamad; Ballal, Mohammad (جامعة بوليتكنك فلسطين - هندسة حاسوب, 2023)
Paint is a covering that protects wooden, iron, and other surfaces while also adding aesthetic appeal. The color is what draws your attention first when you look at any surface or object.When you consider the painting process in its entirety, it is not a simple one because it requires experts into achieve the desired outcome. Especially if you need a color which is not normal, and what is meant is the out- come of combining various colors. Manually combining several colors to create a new color is not an accurate production method. As a result, we are going to create a unique device for combining colors to create a color that is selected from an application linked to the device, or by identifying an existing color through the color sensor and sending the color code using color theory. Based on this, different ratios of the primary colors CMYK are used. The goal of this device is to achieve the required color accurately while saving effort and time. KEYWORDS: PAINT, SURFACES, COLOR, MIXING, SENSOR .
no of pages 70, هندسة حاسوب 12/2023
Keywords: Color Mixing; Machine For Achieving Your Desired Color